2020
DOI: 10.1109/jstsp.2020.3001737
|View full text |Cite
|
Sign up to set email alerts
|

Prior-Guided Image Reconstruction for Accelerated Multi-Contrast MRI via Generative Adversarial Networks

Abstract: Multi-contrast MRI acquisitions of an anatomy enrich the magnitude of information available for diagnosis. Yet, excessive scan times associated with additional contrasts may be a limiting factor. Two mainstream frameworks for enhanced scan efficiency are reconstruction of undersampled acquisitions and synthesis of missing acquisitions. Recently, deep learning methods have enabled significant performance improvements in both frameworks. Yet, reconstruction performance decreases towards higher acceleration facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
58
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 64 publications
(67 reference statements)
0
58
0
Order By: Relevance
“…Recently, research has shown that MC brain images from the same patient contain redundant information, which means that a previously scanned contrast can be used as prior knowledge to reconstruct the images of subsequent contrast scans, consequently further accelerating the MC‐MRI protocols 17–20 . Leveraging shareable information among MC images for fast MRI has been studied using compressed sensing (CS), 20–23 patch‐based operators 7 and dictionary learning 24 methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, research has shown that MC brain images from the same patient contain redundant information, which means that a previously scanned contrast can be used as prior knowledge to reconstruct the images of subsequent contrast scans, consequently further accelerating the MC‐MRI protocols 17–20 . Leveraging shareable information among MC images for fast MRI has been studied using compressed sensing (CS), 20–23 patch‐based operators 7 and dictionary learning 24 methods.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, deep neural networks have been exploited for fast MC images synthesis 25–27 and reconstruction 28–37 . Rather than using fixed, handcrafted extractors, the networks learn the parameters of convolutional kernels for the shareable feature representations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GAN learns data distribution from training samples and can generate realistic imaging data that are similar in distribution, but nevertheless differ from the original data; this may constitute an attractive solution of overfitting for small datasets 13 , 14 . GAN has been applied for reconstructing multi-contrast MR images 16 18 , reducing noise 19 , detecting 20 , 21 , and tumor grading 22 , but assessment of the morphologic characteristics of GAN-based synthetic data and their ability to classify molecular subtype in a diagnostic models have not been tested. If GAN-generated imaging data reflect the morphologic characteristics of glioblastomas with mutant IDH, while varying in morphologic distribution, then these GAN-generated data can be used for training on future deep learning tasks.…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that Mardani suggests the discriminator outputs can be used to focus on sensitive anatomies. Dar et al [100] also used perceptual priors in their multi-contrast reconstruction GAN. The above mentioned studies using GANs have demonstrated enhanced performance compared to state of the art compressed sensing and other parallel imaging reconstruction techniques.…”
Section: Introductionmentioning
confidence: 99%